1984
DOI: 10.1177/107110078400400504
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Chevron and Mitchell Osteotomies for Hallux Valgus

Abstract: A retrospective study of 15 Mitchell and 15 Chevron osteotomies was undertaken in order to compare the efficacy of these two procedures in the correction of hallux valgus. Patient satisfaction, clinical findings, and roentgenographic measurements were all carefully evaluated after follow-up periods of 21 +/- 5 months for the Chevron and 34 +/- 8 months for the Mitchell procedures. Differences observed were a better correction of the angle between the first and second metatarsals by the Mitchell osteotomy (2.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…8,15,23 Consistent with previous reports, transfer metatarsalgia was also the most commonly observed complication in our study, occurring in 36 (60%) patients in the MO group, whereas there were only 5 cases of postoperative metatarsalgia in the CO group.…”
Section: Discussionsupporting
confidence: 93%
“…8,15,23 Consistent with previous reports, transfer metatarsalgia was also the most commonly observed complication in our study, occurring in 36 (60%) patients in the MO group, whereas there were only 5 cases of postoperative metatarsalgia in the CO group.…”
Section: Discussionsupporting
confidence: 93%
“…23 It has been reported that a shift of more than two-thirds of the width of the metatarsal or a shortening of more than .5 mm involves greater risk of nonunion, unstable fixation, and transfer metatarsalgia. 11,16,18,24,25,27 In an unpublished retrospective study of six severe cases (11 feet) of hallux valgus that were treated with Mitchell osteotomy, we found that with 1M angles of more than 20°it was hard to avoid either undercorrection (residual 1M angles of more than 10°), or overshifting and shortening of the metatarsal. Except for the two cases of infection, all of our cases involving complications or dissatisfaction occurred in the group having problems of shifting or shortening.…”
Section: Discussionmentioning
confidence: 95%
“…Secondary transfer metatarsalgia probably accounts for a significant proportion of failure after HV correction. An incidence of 5% to 45% has been reported after the Mitchell osteotomy (1,6,11,12). In contrast, the reported incidence of transfer metatarsalgia after chevron osteotomy has been 0% to 5% (13,14).…”
mentioning
confidence: 97%